A Flexible and Reliable Distributed Multimedia System For Multimedia Information Superhighways - Won-Ki Hong, James; Yun, Tae-Hyoung; Kong, Ji-Young; Shin, Young-Mi (Malaysian Journal of Computer Science, 1997)
Multimedia applications are being developed and used for many aspects of our lives today. New high-speed, broadband networks have emerged and made the operation of these high-bandwidth requiring applications readily feasible. However, the development of distributed multimedia applications and efficient and reliable operation of these applications are still very difficult. This paper presents a flexible and reliable distributed multimedia system that provides a rich multimedia API and that provides distributed multimedia services which can be used to develop a variety of multimedia applications easily. The system as well as applications running on it are managed and controlled in order to provide a reliable and efficient multimedia operations environment. We validate our claim by developing a number of multimedia applications using our distributed multimedia system and by using them for supporting distributed collaborative research experiments on top of a high-speed, broadband information superhighway.